(untitled) (DAPesquisa, 2020)
This essay presents an analysis of the procedures adopted by the german director Erwin Piscator in the adaptive processes of the plays Rasputín (1927) and The Adventures of the Good Soldier Schweik (1927). The procedures employed by Erwin Piscator can be regarded as pioneers of the actor’s dramaturgical creation processes developed by contemporaneous authors, but from the director’s viewpoint.